Synthesis and characterization of inorganic K3Bi2I9 perovskite thin films for lead-free solution processed solar cells. (2021) - Nair, Shruthi; Bhorde, Ajinkya; Kulkarni, Rupali; Bade, Bharat; Punde, Ashvini; Vairale, Priti; Hase, Yogesh; Waghmare, Ashish; Waykar, Ravindra; Deshpande, Mrinalini; Prasad, Mohit; Jadkar, Sandesh
Abstract: Bismuth halide perovskites have been proposed as a non-toxic and chemically stable alternative to lead halide perovskites. Despite being highly stable, the devices based on bismuth perovskites have not been able to compete with the lead counterparts in terms of its efficiencies. The compounds that have been extensively studied i.e. Cs3 Bi2 I9 and MA3 Bi2 I9 form 0D (dimer) structures that possess wide indirect band gaps and poor charge transport properties which hinders the performance of devices based on these materials. Theoretical studies have revealed that replacing bigger A cation like Cs/MA by smaller cation like potassium (K) could favor the formation of layered 2D structures rather than 0D structure. We have synthesized inorganic K3 Bi2 I9 perovskite thin films by facile one-step spin coating method and investigated its structural, optical and morphological properties. The fabricated films showed strong absorption in UV and visible region of solar spectrum and possess optical band gap ∼2 eV. On comparison with the Cs analogue, it is observed that reduction in the cation size (Cs to K) hardly changes the band gap of K3 Bi2 I9 films which implies that the band gap of A3 Bi2 I9 perovskite is insensitive to A-site variation. Films deposited on preheated substrates showed comparatively good coverage without voids on the film surface. Our preliminary studies on this material showed that the films deposited by one-step solution method favored 0D structure rather than the expected 2D layered structure.